(untitled) (European Science Methodical Journal, 2025)
The use of language portfolios in educational and cognitive activities has gained significant attention as an effective tool for student-centered learning. This approach enables students to document their progress, reflect on their achievements, and develop metacognitive skills, fostering autonomy and self-directed learning. The didactic features of language portfolios lie in their ability to integrate assessment with learning, providing a continuous and formative evaluation method. This paper explores the role of language portfolios in enhancing students’ linguistic competence, motivation, and engagement in educational activities. The study also examines the impact of portfolio-based learning on students’ cognitive development and its implementation in pedagogical practice. Drawing from theoretical and empirical research, the article highlights the advantages and challenges associated with using language portfolios in higher education. The findings suggest that this approach contributes to a more personalized and reflective learning process, reinforcing students’ responsibility for their academic growth.